Antifungal, antioxidant and photocatalytic activities of zinc nanoparticles synthesized by Sargassum vulgare extract. (October 2020) - Karkhane, Maryam; Lashgarian, Hamed Esmaeil; Mirzaei, Seyedeh Zahra; Ghaffarizadeh, Azin; cherghipour, Kourosh; Sepahvand, Asghar; Marzban, Abdolrazagh
Abstract: Zinc oxide nanoparticles (ZnO-NPs) have attracted considerable interest owing to their physicochemical properties and vigorous biological activity. In this research, ZnO-NPs were synthesized using aqueous extract of Sargassum vulgare (SVE) as a reducing and capping agent. Morphological and physical features were analyzed through Uv–visible, SEM, TEM, XRD, EDX, DLS and zeta potential studies. Subsequently, antifungal, antioxidant, cytotoxicity and photocatalytic activities were evaluated. FTIR and Uv–vis spectra showed absorption peaks of SVE metabolites and biosynthesized ZnO-NPs before and after the formation of NPs. According to the SEM and TEM micrographs, the biosynthesized ZnO-NPs were spherical with a diameter of about 50–150 nm. The XRD Spectrum indicated the existence of eight peaks corresponding to the crystal angle of the ZnO-NPs. The EDX analysis confirms the presence of oxygen and zinc in the ZnO-NPs structure. The DLS and Zeta potential revealed that the hydrodynamic diameter of ZnO-NPs was approximately 200 nm and +12.7 mV, respectively. The ZnO-NPs demonstrated wide-spectrum antifungal action against Aspergillus, Candida and saccharomyces cerevisiae . The antioxidant potential of ZnO-NPs was determined to be around 65% lower than that of ascorbic acid and BHA, but higher than that of SVE. The cytotoxic effect of ZnO-NPs against the HepG2 cell line was estimated to be an IC50 value of 128.0 μg/ml. Given the potent antioxidant and photocatalytic capacity as well as the robust antifungal activity of ZnO-NPs, a broad variety of applications such as the biological control of plant diseases and the removal of pesticide residues may be recommended. Graphical abstract: Image 1 Highlights: Phyco-fabrication of ZnO nanoparticles was successfully performed using aqueous extract of Sargassum vulgar. ZnO-NPs were physicochemically and biologically well-characterized. The antifungal, antioxidant and catalytic activities of ZnO-NPs were found to be remarkable.